Selection of ideal sites for the development of large-scale solar photovoltaic projects through Analytical Hierarchical Process – Geographic information systems (AHP-GIS) in Peru. (October 2021) - Rios, R.; Duarte, S.
Abstract: Considering the growing energy demand and the effects of climate change, the proper selection of sites for the installation of clean technology projects takes on a special importance, especially in Peru, a mega diverse country with high potential for the exploitation of renewable resources and with the urgent need of protecting their natural heritage. This article details the methodology for obtaining suitable sites for the development of large-scale photovoltaic solar projects, through the combination of multi-criteria analysis and Geographic Information Systems (GIS), being this the first experience on the subject nationwide. Information regarding 33 restriction factors and 7 criteria were identified and systemized, with the criteria being analyzed using the Analytical Hierarchy Process (AHP). To obtain the relative weight of each criterion, a survey was designed, which was administered to national experts related to renewable energies and solar projects. The final suitability map was grouped into five categories: "Highly Adequate", "Very Adequate", "Adequate", "Marginally Adequate" and "Inadequate". As a result, 69.52% of the country was excluded from the AHP analysis, with around 22 257 km 2 of the remaining area considered areas of high potential as "Highly Adequate" (0.09%) or "Very Adequate" (5.55%), being located in areas adjacent to the transmission system in the southern region, as well as in the north and central coast of the country. The comparison with the location of the large-scale photovoltaic installations already operational and the sensitivity analysis performed gave confidence to the results. The methodology used allows its improvement over time, as well as the intervention of stakeholders and its replicability for other renewable energy systems. Highlights: First experience identifying suitable sites for photovoltaic power plants in Peru with multi-criteria decision making. Analytical hierarchy process and geographic information systems were used to assess multiple categories of criteria. 69.52% of Peru was considered restricted area as a way to protect the ecosystems. Approximately 22 257 km 2 were considered high potential areas for large-scale photovoltaic power plants. Good correlation between potentially suitable areas and current photovoltaic power plant installations.